The Body as a Factory and the Surgeon as its Architect - Pera, Cristóbal (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
If the human body is really a fabric, should surgeons be considered architects? The author raises and analyzes this question, and he concludes that surgeons cannot be considered as such: the architect is the creator of his work, but the surgeon is not the creator of this complex biological fabric which is the human body. They heal wounds, align fractured bones, and cuts open to reach its internal organs; explore the body, reconstruct its ailing parts, substitute vital organs taken from a donor’s foreign body, design prostheses, and replace damage body parts. Other surgeons retouch its aging façade, looking for an iconic and timeless beauty. The surgeon cannot put from scratch,a biological fabric so he can’t create the subject of his work as an architect can create a building. In contrast, the surgeon restores the body’s deteriorated or damaged parts and modifies the appearance of the body’s façade.